Eps1, a novel PDI-related protein involved in ER quality control in yeast. - Wang, Q (1999)
PMA1 is an essential gene encoding the yeast plasma membrane [H(+)]ATPase. A pma1-D378N mutant has a dominant-negative effect on cell growth because both newly synthesized mutant and wild-type Pma1 molecules are retained and degraded in the endoplasmic reticulum (ER). Like other substrates for ER-associated degradation, Pma1-D378N is stabilized in mutants defective in components of the ubiquitination machinery. A genetic selection was performed for eps (ER-retained pma1 suppressing) mutants in which the growth defect caused by the D378N allele is suppressed. In an eps1 mutant, both mutant and wild-type Pma1 molecules are allowed to travel to the plasma membrane; however, normal retention of resident ER proteins Shr3 and Kar2 is not perturbed. Eps1 is a novel membrane protein belonging to the protein disulfide isomerase (PDI) family, and Eps1 co-localizes with Pma1-D378N in the ER. In the absence of Pma1-D378N, ER export of wild-type Pma1 is not affected by eps1 deletion, but export of the plasma membrane protein Gas1 is delayed. Because Eps1 is required for retention and degradation of Pma1-D378N, we propose a model in which Eps1 acts as a novel membrane-bound chaperone in ER quality control.